ANALYSIS ON THE SUSTAINABLE LIVELIHOOD APPROACH IN RAJA AMPAT - Margaretha Uslin Toam (Jurnal Ilmiah Mahasiswa FEB, 2018)
Tourism has an important role in the economic growth of a region. One of themost popular tourist destinations in Indonesia and has been worldwide is RajaAmpat. Raja Ampat has more than 300 tourist objects and the number of visitorsis increasing every year. Due to its popularity sustainable livelihood approach inRaja Ampat is expected to bring good impact for future generation. The fiveimportant capitals in sustainable livelihood approach. Comprising human capital,natural capital, financial capital, physical capital, and social capital is able toincrease the income of local people, reduce poverty, create employment, createprosperity of the people, preserve cultural values and sustainable economy. Thisstudy employed ethnography approach as the research method which is based onobservation of a group of people in natural environment by conducingobservation, interviews, and documentation on data retrieval techniques. Theresults of observation on five important capitals in sustainable livelihoodapproach, revealed that human capital of the government need to empower thelocal community and prepare the young generation with adequate education. Inaddition the natural capital, community and visitors need to maintain and takecare of surrounding environment around because human life dependents onnature. In terms of financial capital, due to the development of tourism sector inRaja Ampat, local income and local government revenue are increasing. As aresult of the increasing number of tourists visiting Raja Ampa., Physical capitalincluding facilities and infrastructures needs to be developed to support the needsvisitors of Raja Ampat. Social capital that is harmonious and friendly communitywelfare.Keywords: sustainable development, sustainable livelihood, tourism